Education for all: the requirements - Windham, Douglas M. (UNESCO ParisFR, 1992)
Examines four inter-related themes - developing a supporting policy context; mobilizing resources; building national technical capacity; and strengthening international solidarity. Considers how a broad range of personnel can be empowered to provide basic education. Looks at the role and responsibilities of the teachers, together with the conditions of service and work that can enhance the teachers' effectiveness. Discusses the involvement of parents, communities and non-governmental organizations in designing, providing and supporting basic education. Stresses the importance of instructional materials and looks at ways to use technology and assessment capacities to make learning opportunities more available and effective. Reviews the issues of financing, including opportunities for reducing costs and finding alternative sources for funding.